Standardization and a multilaboratory comparison of Neisseria meningitidis serogroup A and C serum bactericidal assays. The Multilaboratory Study Group. - Maslanka, S E (1997)
A standardized serum bactericidal assay (SBA) is required to evaluate the functional activity of antibody produced in response to Neisseria meningitidis serogroup A and C vaccines. We evaluated assay parameters (assay buffer, target strains, growth of target cells, target cell number, complement source and concentration, and methods for growth of surviving bacteria) which may affect the reproducibility of SBA titers. The various assay parameters and specificity of anticapsular antibody to five serogroup A strains (A1, ATCC 13077, F8238, F9205, and F7485) and four serogroup C strains (C11, G7880, G8050, and 1002-90) were evaluated with Centers for Disease Control and Prevention meningococcal quality control sera. The critical assay parameters for the reproducible measurement of SBA titers were found to include the target strain, assay incubation time, and complement. The resulting standardized SBA was used by 10 laboratories to measure functional anticapsular antibody against serogroup A strains F8238 and serogroup C strain C11. In the multilaboratory study, SBA titers were measured in duplicate for 14 pairs of sera (seven adults and seven children) before and after immunization with a quadrivalent polysaccharide (A, C, Y, and W-135) vaccine. The standardized SBA was reliable in all laboratories regardless of experience in performing SBAs. For most sera, intralaboratory reproducibility was +/- 1 dilution; interlaboratory reproducibility was +/- 2 dilutions. The correlation between median titers (interlaboratory) and enzyme-linked immunosorbent assay total antibody concentrations was high for both serogroup A (r = 0.86; P < 0.001; slope = 0.5) and serogroup C (n = 0.86; P < 0.001; slope = 0.7). The specified assay, which includes the critical parameters of target strain, incubation time, and complement source, will facilitate interlaboratory comparisons of the functional antibody produced in response to current or developing serogroup A and C meningococcal vaccines.